CHATBOTS: the technology that is transforming the way we communicate - do Nascimento, Amanda Francieli; Graciano, Fernando Cesar (Revista Interface Tecnológica, 2023)
With the advancement of technology, the internet and mobile devices have played an increasingly important role in society. Among the various technological advances that improve productivity and customer service, the use of chatbots stands out. These programs, which simulate a conversation with a human being, are increasingly common and have the ability to provide specific information and quick responses with a natural language, which significantly improves the user experience. In addition, chatbots offer many other advantages such as 24/7 availability, which means that users can get help at any time with no time restrictions. In this article, bibliographic research methodologies were used, as well as a case study at the institution Fatec Taquaritinga, as well as the analysis and collection of data from the site. In conclusion, a chatbot model will be presented and developed using the javaScript programming language, with the objective of serving the services of the institution of Taquaritinga. It is expected that it will contribute with accurate and quick information to students, as well as to optimize the institution's service flow.
Keywords: Chatbot; Virtual human; . Artificial intelligence; Assistance to students